2020
DOI: 10.1049/iet-map.2019.0876
|View full text |Cite
|
Sign up to set email alerts
|

Multi‐functional sandwich structure with metamaterial antenna lattice cores: protection, radiation and absorption

Abstract: In this study, a multi‐functional sandwich structure is proposed with mechanical support, electromagnetic radiation and absorption by radome‐integrated design of metamaterial antenna array. The pyramid metamaterial absorber (PMA) is used as the radiator of the antenna element, with a fibre‐reinforced resin composite radome attached on the top. To enhance mechanical strength of the radome and meanwhile to reduce radar cross‐section (RCS) of the antenna, the PMA is used as the lattice core of sandwich structure.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Furthermore, one can find that the intensity of some absorption peaks is too large due to the interference of many stray peaks in the test process. 23 In addition, the comparison of the MWAP and large-angle MWAP of this work and similar pyramid MWAP is shown in Table 1 3,4,[23][24][25]44 It can be found that the pyramid has excellent wide bandwidth microwave absorbing ability, which is a promising candidate for broadband and high-efficiency microwave absorber application.…”
Section: Actual Test Of Pyramid Structurementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, one can find that the intensity of some absorption peaks is too large due to the interference of many stray peaks in the test process. 23 In addition, the comparison of the MWAP and large-angle MWAP of this work and similar pyramid MWAP is shown in Table 1 3,4,[23][24][25]44 It can be found that the pyramid has excellent wide bandwidth microwave absorbing ability, which is a promising candidate for broadband and high-efficiency microwave absorber application.…”
Section: Actual Test Of Pyramid Structurementioning
confidence: 99%
“…Generally, the absorbing materials used in anechoic chambers require higher absorptivity and wider absorption bandwidth. The structural design of microwave-absorbing materials is one of the most effective methods. For example, porous structure, , honeycomb, pyramid, hollow pyramid, etc., have been employed in the electromagnetic wave field due to their structural advantages . At present, the processing technology of structural microwave-absorbing materials includes direct three-dimensional (3D) printing molding, model impregnation with microwave-absorbing slurry, one-step injection molding, foaming molding, and so on.…”
Section: Introductionmentioning
confidence: 99%
“…Note that spoof surface plasmon polariton (SSPP) is serving for wideband absorption by virtue of deep-subwavelength and strong local field enhancement properties [18]. The wideband absorption of periodically arranged SSPP framework has been introduced in several recent reference papers [19][20][21][22][23][24]. In this work, we expand on the previous publications to integrate a specific application scene, where an absorbing structure (AS) based on SSPP [24] is applied to realize the aim of wideband suppression of edge diffraction.…”
Section: Introductionmentioning
confidence: 98%
“…Various methods of reducing the RCS of antennas have been proposed in recent years 6–10 . A high‐impedance surface had been used in a patch array antenna, where the surface acts as the superstrate of the antenna to increase its size 6 .…”
Section: Introductionmentioning
confidence: 99%
“…This setup can achieve a maximum reduction of 28 dB in the RCS of the antenna for out‐of‐band use, and cannot reduce its RCS in band at all. Han proposed a pyramid metamaterial absorber‐based low‐RCS antenna with a large profile that can obtain only out‐of‐band RCS reduction 8 . Gabriel et al designed a method to reduce the wideband RCS of an antenna by loading a resistive frequency‐selective surface as superstrate 9 .…”
Section: Introductionmentioning
confidence: 99%